Zero-dispersion limit for integrable equations on the half-line with linearisable data. (13th May 2004) - Fokas, A. S.; Kamvissis, S.
Abstract : We study the zero-dispersion limit for certain initial boundary value problems for the defocusing nonlinear Schrödinger (NLS) equationand for the Korteweg-de Vries (KdV)equation with dominant surface tension. These problems are formulated on the half-line and they involve linearisable boundaryconditions.